Thriving Through Relationships in Sport: The Role of the Parent–Athlete and Coach–Athlete Attachment Relationship - Davis, Louise; Brown, Daniel J.; Arnold, Rachel; Gustafsson, Henrik (Frontiers in Psychology, 2021)
The aim of this research was to examine if attachment relationships to significant others, such as to parents and/or sports coaches enable thriving and competition performance within sport. Two studies employing cross-sectional and prospective designs were carried out across different samples of athletes of varied skill levels and sports. In Study 1, we found athletes’ attachment to their sports coach was significantly associated with athlete thriving and mediated by psychological needs satisfaction. Results of Study 2 found that athletes’ secure attachment to their mother and /or father positively predicted thriving, whilst athletes’ insecure attachment did not predict thriving. Furthermore, athletes’ attachment to both mother and father did not predict competition performance. Together, these two studies acknowledge the significant role that athletes’ secure attachment relationships with parents and coaches play in facilitating athletic thriving. These findings have significant implications for research and practice.